THE EFFECT OF FINS PERFORATION AND MATERIAL TYPE ON THERMAL PERFORMANCE OF A HEAT SINK UNDER NATURAL CONVECTION (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2018)
An experimental study was done to investigate the effect of fin geometrymodification and material type on heat dissipation from a heat sink under natural convection.v-corrugated solid fin and v-corrugated perforated fin were designed for this purpose.Aluminum and Copper metals were selected in designing the fins because their wideapplication in cooling and heating equipment. Three different voltages 110, 150 and 200 Vsupplied to the heat sink to study their effects on the fins performance. Each experimentrepeats two times to reduce the error and the data recorded after reaching the steady stateconditions. The utilization of solid and perforated v-corrugated fins is compared. The resultsshowed that perforated fins dissipated heat more than corresponding solid by 15.4, 34 and32% for aluminum, and 2.7, 2.1 and 4.3% for copper fin in the three voltages. Also, theresults indicated that the heat loss by solid copper fin is greater by 56, 72 and 92% thancorresponding solid aluminum fin and for perforated fin case by 38, 31.7 and 51.9 % at110,150 and 200 V respectively.